Binomial Coefficient Challenge 5!

Let

S ( m ) = k = 0 m ( m k ) 2 m + 1 2 m + 1 k ( 2 ) k S(m) = \displaystyle \sum_{k=0}^m{\binom{m}{k} \frac{2m+1}{2m+1-k} {(-2)}^k}

If

m = 0 S ( m ) 2 m = a b ( 1 1 c tanh 1 1 c ) , \sum_{m=0}^\infty S(m) 2^{-m} \; =\; \frac{a}{b} \left(1 - \frac{1}{\sqrt{c}}\tanh^{-1}\tfrac{1}{\sqrt{c}}\right),

where a a and b b are positive coprime integers and c c is not divisible by the square of any prime, then find a + b + c a + b + c .

Details and Assumptions

  1. You may use a computer to complete the final step but you should know the method to complete the challenge.

  2. tanh 1 ( x ) = 1 2 ln ( 1 + x 1 x ) \tanh^{-1}(x) = \frac{1}{2} \ln\left(\frac{1+x}{1-x}\right)


The answer is 8.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Mark Hennings
Jun 8, 2017

Note that S ( m ) 2 m + 1 = k = 0 m ( m k ) ( 2 ) k 2 m + 1 k = 0 1 k = 0 m ( m k ) ( 2 ) k t 2 m k d t = 0 1 t 2 m ( 1 2 t 1 ) m d t = 0 1 ( t 2 2 t ) m d t = 0 1 ( u 2 1 ) m d u \begin{aligned} \frac{S(m)}{2m+1} & = \sum_{k=0}^m \binom{m}{k}\frac{(-2)^k}{2m+1-k} \; = \; \int_0^1 \sum_{k=0}^m \binom{m}{k} (-2)^k t^{2m-k}\,dt \\ & = \int_0^1t^{2m}(1 - 2t^{-1})^m\,dt \; =\; \int_0^1(t^2-2t)^m\,dt \; = \; \int_0^1 (u^2-1)^m\,du \end{aligned} for any m 0 m \ge 0 . Thus m = 0 S ( m ) 2 m + 1 x 2 m + 1 = m = 0 x 2 m + 1 0 1 ( u 2 1 ) m d u = 0 1 x d u 1 x 2 ( u 2 1 ) = 0 1 x d u 1 + x 2 x 2 u 2 = 1 1 + x 2 tanh 1 x 1 + x 2 \begin{aligned} \sum_{m=0}^\infty \frac{S(m)}{2m+1}x^{2m+1} & = \sum_{m=0}^\infty x^{2m+1}\int_0^1 (u^2-1)^m\,du \; = \; \int_0^1 \frac{x\,du}{1 - x^2(u^2-1)} \\ & = \int_0^1 \frac{x\,du}{1+x^2 - x^2u^2} \; = \; \frac{1}{\sqrt{1+x^2}} \tanh^{-1}\frac{x}{\sqrt{1+x^2}} \end{aligned} for any x < 1 |x| < 1 . Differentiating within the radius of convergence, we obtain m = 0 S ( m ) x 2 m = 1 1 + x 2 [ 1 x 1 + x 2 tanh 1 x 1 + x 2 ] x < 1 \sum_{m=0}^\infty S(m)x^{2m} \; = \; \frac{1}{1+x^2}\Big[ 1 - \frac{x}{\sqrt{1+x^2}}\tanh^{-1}\frac{x}{\sqrt{1+x^2}}\Big] \hspace{1cm} |x| < 1 Putting x = 1 2 x = \tfrac{1}{\sqrt{2}} gives m = 0 S ( m ) 2 m = 2 3 [ 1 1 3 tanh 1 1 3 ] \sum_{m=0}^\infty S(m) 2^{-m} \; = \; \tfrac23\Big[1 - \tfrac{1}{\sqrt{3}}\tanh^{-1}\tfrac{1}{\sqrt{3}}\Big] making the answer 2 + 3 + 3 = 8 2 + 3 + 3 = \boxed{8} .

From the integral representation of S ( m ) S(m) it is easy to show that S ( m ) = ( 4 ) m ( 2 m m ) m 0 S(m) \; = \; \frac{(-4)^m}{\binom{2m}{m}} \hspace{2cm} m \ge 0

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...